Visible light‐induced photocatalytic and antibacterial activity of N‐doped TiO2. Issue 2 (14th May 2019) - Iwatsu, Misato; Kanetaka, Hiroyasu; Mokudai, Takayuki; Ogawa, Toru; Kawashita, Masakazu; Sasaki, Keiichi
Abstract: Previous reports of some studies have described that nitrogen (N)‐doped titanium dioxide (TiO2 ) exhibits photocatalytic antibacterial activity under visible light irradiation and that reactive oxygen species (ROS) is involved in its activity. For prevention and treatment of peri‐implantitis, an inflammatory lesion caused by the bacterial infection of plaque adhering to the circumference of an implant, we considered that applying N‐doped TiO2 to dental implant surfaces can be effective. For this study, we aimed at evaluating visible light‐induced antibacterial activity of titanium (Ti) treated with NaOH and hot water, and subsequently heated in an ammonia (NH3 ) gas atmosphere at 500°C for 3 hr to quantify the generated amount of ROS available for antibacterial activity. N‐doped anatase‐type titania (TiO2 ‐xNx) is formed on the Ti substrate surface. Under visible light, markedly more hydroxyl radicals were generated with a nitrogen‐doped titanium dioxide plate than with a pure titanium plate. Hydrogen peroxide exhibited the same tendency. Furthermore, it showed visible light‐induced antibacterial effects over Escherichia coli . Results demonstrate that N‐doped TiO2 can be useful as a dental implant surface with low risk of postoperative infection when using visible light irradiation.